Maternal death after oocyte donation at high maternal age: case report - Steegers Eric AP; Schuitemaker Nico WE; Schutte Joke M; van Roosmalen Jos (BMC, 2008)
Abstract Background The percentage of women giving birth after the age of 35 increased in many western countries. The number of women remaining childless also increased, mostly due to aging oocytes. The method of oocyte donation offers the possibility for infertile older women to become pregnant. Gestation after oocyte-donation-IVF, however, is not without risks for the mother, especially at advanced age. Case presentation An infertile woman went abroad for oocyte-donation-IVF, since this treatment is not offered in The Netherlands after the age of 45. The first oocyte donation treatment resulted in multiple gestation, but was ended by induced abortion: the woman could not cope with the idea of being pregnant with twins. During the second pregnancy after oocyte donation, at the age of 50, she was mentally more stable. The pregnancy, again a multiple gestation, was uneventful until delivery. Immediately after delivery the woman had hypertension with nausea and vomiting. A few hours later she had an eclamptic fit. HELLP-syndrome was diagnosed. She died due to cerebral haemorrhage. Conclusion In The Netherlands, the age limit for women receiving donor oocytes is 45 years and commercial oocyte donation is forbidden by law. In other countries there is no age limit, the reason why some women are going abroad to receive the treatment of their choice. Advanced age, IVF and twin pregnancy are all risk factors for pre-eclampsia, the leading cause of maternal death in The Netherlands. Patient autonomy is an important ethical principle, but doctors are also bound to the principle of 'not doing harm', and do have the right to refuse medical treatment such as IVF-treatment. The discussion whether women above 50 should have children is still not closed. If the decision is made to offer this treatment to a woman at advanced age, the doctor should counsel her intensively about the risks before treatment is started.